2004
DOI: 10.1002/ana.20285
|View full text |Cite
|
Sign up to set email alerts
|

A novel endogenous erythropoietin mediated pathway prevents axonal degeneration

Abstract: Clinically relevant peripheral neuropathies (such as diabetic and human immunodeficiency virus sensory neuropathies) are characterized by distal axonal degeneration, rather than neuronal death. Here, we describe a novel, endogenous pathway that prevents axonal degeneration. We show that in response to axonal injury, periaxonal Schwann cells release erythropoietin (EPO), which via EPO receptor binding on neurons, prevents axonal degeneration. We demonstrate that the relevant axonal injury signal that stimulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
117
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 44 publications
4
117
0
Order By: Relevance
“…100 Beneficial effects of both EPO and its nonhematopoietic derivatives and mimetics have been described in models of peripheral axonal nerve injury, injury-induced Wallerian degeneration, diabetic, and HIV-associated neuropathy. 41,[101][102][103][104][105] In these conditions, the anti-cytokine, antiapoptotic, anti-oxidative, and trophic effects on both neurons and oligodendrocyte progenitor cells are likely to reduce inflammation and preserve myelination and neuronal function. 33,67,[91][92][93][94][95][96][97][98]102,103 The initial observation by Grimm et al 106 of a potent neuroprotective effect of EPO in light-induced retinal degeneration has been confirmed in many other models of retinal disease in which EPO derivatives are in consideration for clinical use.…”
Section: Neuroinflammation Retinal Disease and Peripheral Nerve Damagementioning
confidence: 99%
“…100 Beneficial effects of both EPO and its nonhematopoietic derivatives and mimetics have been described in models of peripheral axonal nerve injury, injury-induced Wallerian degeneration, diabetic, and HIV-associated neuropathy. 41,[101][102][103][104][105] In these conditions, the anti-cytokine, antiapoptotic, anti-oxidative, and trophic effects on both neurons and oligodendrocyte progenitor cells are likely to reduce inflammation and preserve myelination and neuronal function. 33,67,[91][92][93][94][95][96][97][98]102,103 The initial observation by Grimm et al 106 of a potent neuroprotective effect of EPO in light-induced retinal degeneration has been confirmed in many other models of retinal disease in which EPO derivatives are in consideration for clinical use.…”
Section: Neuroinflammation Retinal Disease and Peripheral Nerve Damagementioning
confidence: 99%
“…68 EPO inhibits axonal degeneration and therefore may be therapeutically useful in a wide variety of human neurological diseases characterized by axonopathy. 69 In clinical studies, stroke patients receiving recombinant human EPO (rHuEPO) within 5 hours of the onset of cerebral ischemic symptoms showed a significantly improved clinical progress, as well as a reduced infarct size as measured by MRI, compared with placebo-treated patients. 65 The Gottingen EPO Stroke Study, a multicenter pilot study for proof of concept (preceding the necessary phase III trial), is ongoing in Germany.…”
Section: Erythropoietinmentioning
confidence: 99%
“…However, several studies have suggested the critical importance of endogenous EPO production for ischemic tolerance, via EPO-induced JAK-2, STAT5, and NF-κB phosphorylation within neurons (6,(10)(11)(12). Astrocytes are the major source of EPO production within the brain (12), whereas Schwann cells seem to be the major source in the peripheral nervous system (13,14).…”
mentioning
confidence: 99%
“…In addition, EPO has been shown to robustly prevent axonal degeneration, independent of neuronal death (14,19). This is therapeutically relevant, given that axonal loss is a prominent cause of disability in several human neurologic diseases, including diabetic peripheral neuropathy, multiple sclerosis, and Alzheimer's disease, and often precedes neuronal death by several years in these diseases (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation